Low waist circumference prior to percutaneous coronary intervention predict the risk for end-stage renal disease: a nationwide Korean population based-cohort study - Eun Hui Bae; Sang Yup Lim; Eun Mi Yang; Tae Ryom Oh; Hong Sang Choi; Chang Seong Kim; Seong Kwon Ma; Bongseong Kim; Kyung-Do Han; Soo Wan Kim (The Korean Journal of Internal Medicine, 2022)
Background/Aims The obesity paradox has been known in end-stage renal disease (ESRD). However, the effect of body mass index (BMI) or waist circumference (WC) prior to percutaneous coronary intervention (PCI) on the development of ESRD is not clear. Methods Using nationally representative data from the Korean National Health Insurance System, we enrolled 140,164 subjects without ESRD at enrolment who underwent PCI between 2010 and 2015, and were followed-up until 2017. Patients were stratified into five levels based on their baseline BMI and six levels based on their WC with 5-cm increments. BMI and WC were measured at least 2 years prior to PCI. The primary outcome was the development of ESRD. Results During a median follow-up of 5.4 years, 2,082 (1.49%) participants developed ESRD. The underweight group (hazard ratio [HR], 1.331; 95% confidence interval [CI], 0.955 to 1.856) and low WC (< 80/< 75) (HR, 1.589; 95% CI, 1.379 to 1.831) showed the highest ESRD risk and the BMI 25 to 30 group showed the lowest ESRD risk (HR, 0.604; 95% CI, 0542 to 0.673) in all participants after adjusting for all covariates. In the subgroup analysis for diabetes mellitus (DM) duration, WC < 85/80 cm (men/women) increased ESRD risk in only the DM group (DM < 5 years and DM ≥ 5 years) compared to the reference group (85–90/80–85 of WC), but not the normal or impaired fasting glucose group. Conclusions Low WC prior to PCI showed an increased ESRD risk in patients with DM undergoing PCI as compared to those without DM.